A Study on Marketing Pattern of Chilli Cultivation in Wokha District of Nagaland, India - Murry, Nchumthung; Tsopoe, James (International Journal of Economic Plants, 2020)
The present research was conducted in Wokha district of Nagaland during the year 2015-16 to understand and analysis the pattern of marketing of chilli. Altogether 60 chilli growers were identified by following multi-stage stratified random sampling method. The identified chilli growers were grouped into three categories viz., marginal (2.01 ha) based on area of chilli cultivation owned by the respondents. From the study two marketing channels of chilli were identified in the study area viz., Producer - Consumer (Channel I), Producer - Retailer - Consumer (Channel II). It was found out that the producer share in consumer rupee was higher in channel – I which was as high as 80.00% as compared to that of channel – II which was only 57.14%. Marketing efficiency estimated by Shepherd’s formula revealed that marketing efficiency was higher in channel - I (39.02 %) as compared to channel - II (18.67%).